COVID-19 Infodemic in Indonesia: Impacts on National Security and Government Responses - Hennida, Citra; Inas Pratiwi, Fadhila; Rokhmawati Susanto, Siti; Atsir, Salmavira; Eno Nabilah, Amelia; Sugianto Putri, Rizky; Yuni Ekasari, Devi (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2025)
The infodemic, characterised by widespread misinformation and disinformation about COVID-19, including its transmission and vaccines, was a significant issue in Indonesia from 2020 to 2023, during and after the pandemic. This research aims to analyse the impact of the infodemic on Indonesia's national security during this critical period, emphasising the importance of understanding how infodemic can influence national security. This article presents a rigorous literature review and process tracing method, collecting data from various stakeholders, journal articles, news media, and reports from international organisations to explore the correlations between infodemic and national security. It argues that Indonesia's extensive social media landscape and low public health literacy levels have intensified the spread of viral misinformation, undermining the pandemic response. The government's initiatives to combat the infodemic were successful, as evidenced by increased compliance with COVID-19 protocols and vaccination participation. The article is organised into four sections. The first discusses misinformation in Indonesia and offers a literature review. The second explores theoretical arguments regarding the infodemic's impact on national security. The third examines government responses and stakeholder involvement. The final section analyses the effectiveness of these efforts.